Dampak Dan Etika Penerapan Dari AI Pada Bidang Akuntansi: Systemattic Literature Review - Rr. Puteri Aida Laily Inas; Dona Primasari (AKUNTANSI 45, 2025)
This study explores the role of Artificial Intelligence (AI) in accounting, focusing on the impact and ethics of its implementation. This study uses a secondary approach or uses systematic literature reflection and collects data from various reputable sources such as Scholar. This review identified 20 relevant articles from 2020 to 2024 which were analyzed to match the research questions. The findings highlight the potential of AI to improve the advantages and disadvantages of AI in accounting. This study discusses the application of AI integration, emphasizing the need for ethical considerations and regulatory adjustments. Overall, the results of this study explain the impact of AI in accounting such as increased efficiency, reduced costs, increased accuracy, corporate decision-making, and increased security. Then the ethics in dealing with accounting AI are confidentiality, accuracy and clarity, transparency, accountability, and compliance with regulations.